2009
DOI: 10.1345/aph.1l578
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in Combat-Related Posttraumatic Stress Disorder

Abstract: When used in addition to other empiric therapy, topiramate may be effective at reducing general symptoms of combat-related PTSD and reducing high-risk alcohol intake and nightmares. Further randomized controlled trials of topiramate for the treatment of combat-related PTSD are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…While case series suggested that adjunctive topiramate [1026,1027,1029] may be effective in treatment-resistant PTSD, a RCT failed to show superiority over placebo [1028] (Level 2, negative).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…While case series suggested that adjunctive topiramate [1026,1027,1029] may be effective in treatment-resistant PTSD, a RCT failed to show superiority over placebo [1028] (Level 2, negative).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Topiramate has shown partial effectiveness in reducing PTSD symptoms in patients without AUD in three open trials (Berlant and van Kammen, 2002, Berlant, 2004, Alderman et al, 2009) and three small-to-medium sized controlled trials (Lindley et al, 2007, Tucker et al, 2007, Yeh et al, 2011). In a placebo-controlled trial in veterans, topiramate treatment was associated with greater improvement in PTSD re-experiencing symptoms when used to augment standard PTSD pharmacotherapy, although with more adverse effects and higher dropout (Lindley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There have been no controlled trials of topiramate to examine its effects in reducing alcohol consumption and PTSD symptom severity in patients with co-occurring AUD and PTSD, although a small open trial of topiramate in male combat veterans with PTSD showed a reduction in PTSD symptoms and a decrease in the proportion of patients with high-risk drinking (defined as >43 drinks/week) (Alderman et al, 2009). We therefore conducted a randomized, placebo-controlled pilot trial to provide a preliminary assessment of the efficacy, and safety of topiramate during a 12-week course of treatment in 30 veterans with PTSD and AUD whose treatment goals were to reduce and possibly stop alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Other promising pharmacotherapies of comorbid PTSD and SUD include, for instance, quetiapine, an antipsychotic medication (Monnelly et al 2004) and topiramate, an antiseizure medication (Alderman et al 2009), but the safety and efficacy of these medications for the treatment of posttraumatic stress disorders and SUD need to be tested in controlled clinical trials.…”
Section: Pharmacotherapymentioning
confidence: 99%